P74 Complement variations in systemic lupus erythematosus pregnancies. (23rd March 2020) - Crisafulli, Francesca; Andreoli, Laura; Filippini, Matteo; Fredi, Micaela; Gerardi, Maria Chiara; Gorla, Roberto; Lazzaroni, Maria Grazia; Nalli, Cecilia; Taglietti, Marco; Lojacono, Andrea; Zatti, Sonia; Franceschini, Franco; et al.
Abstract : Background/Purpose: To analyse complement variations during SLE pregnancies, considering pregnancies with Adverse Pregnancy Outcome (APO) and with flares. Methods: Monocentric, retrospective study of 98 SLE patients with 134 pregnancies (including 3 twin pregnancies) prospectively followed by multidisciplinary team (1987–2015). Hypocomplementemia was defined according to the normality range calculated in healthy pregnancies by Reggia et al . 1 Results: APO occurred in 22 (16%) and flares in 11 (8%) pregnancies. The variation of mean C3 and C4 levels are shown in table 1 . Notably, both in pregnancies with flares and with APO, there was no increase of C3 between the 2nd and the 3rd trimester and of C4 between the 1st and the 3rd trimester. In pregnancies with flares the mean levels of C3 and C4 were lower than in pregnancies without flares during the 2nd and the 3rd trimester; the mean levels of C4 were also lower in the flare group during pre-conceptional visit. In pregnancies with APO, the variation of C4 levels between the 2nd and the 3rd trimester was lower than in pregnancies without APO (-3.18 vs 0.27; p=0.01). The frequency of low C4 was higher in pregnancies with flare at pre-conceptional visit, 1st trimester and 3rd trimester (6/7 vs 25/103 p=0.002; 8/9 vs 56/106 p=0.04; 9/11 vs 33/96 p=0.003), as compared with pregnancies without flares. Conclusions: In our cohort, low C4 at pre-conceptional visit seems to predict flares during pregnancies. Lower increase of C4 levels between the 2nd and the 3rd trimester could predict an APO. Reference: Reggia R., Ziglioli T., Andreoli L., et al. Primary anti-phospholipid syndrome: any role for serum complement levels in predicting pregnancy complications?. Rheumatology 2012;51:2186–2190